Chapter Towards new marine-coastal Natura 2000 sites in the central Adriatic Sea. - Chiuchiarelli, Igino (Proceedings e report, 2020)
LIFE17 NAT/IT/000565 CALLIOPE aims to improve the coast-sea regional natural connectivity by improving the Natura 2000 Network. The main objectives are: improving the biodiversity knowledge of marine environments, testing integrated management strategies to increase the conservation of coastal-marine biodiversity and supporting the preparation of a Coastal Action Plan for the Abruzzo Region. We identified and mapped the HD-1110 here dominated by Cymodocea nodosa, the HD-1160 with the presence Zostera noltii and in correspondence of rocky environments the HD-1170.